Help me simplify this down some more so I can set it to zero and find my critical points.

f(x) = x^3 (x+2)^6

f'(x) = x^3 * 6(x+2)^5 + 3x^2 * (x+2)^6

2 answers

I see a common factor of 3x^2(x+2)^5

so
x^3 * 6(x+2)^5 + 3x^2 * (x+2)^6

= 3x^2(x+2)^5[2x + x+2}
= 3x^2(x+2)^5(3x+2)
Thanks.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. 1. Subtract and simplify18/y-8 - 18/8-y 2. subtract simplify if possible v-5/v - 7v-31/11v 3. Simplify by removing factors of 1
    1. answers icon 2 answers
  4. 1. divide and simplify x^2+x-56/x^1-1 / x-7/2x+22. find the product in simplest from for x^2+x-6/2x^2-x-3 * x^7-2x^6+4x^5/x^4+8x
    1. answers icon 4 answers
more similar questions